2011
DOI: 10.1177/0300985811424732
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Lesions in Fetal Brains Following Experimental Infection of Pregnant Sheep With Toxoplasma gondii

Abstract: Six ovine fetal brains were harvested 33 to 35 days postchallenge from 5 ewes, each of which was given 3000 Toxoplasma gondii oocysts on day 90 of pregnancy. Histopathologic examination of transverse sections taken at 13 levels in the fetal brains revealed the presence of toxoplasmosis-related lesions in all 6 brains. However, lesions were not randomly distributed (P ¼ .007); they were most numerous at the level of the optic tract, the rostral margin of the pons, and 4 mm caudal to the ansate sulcus and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…ELISA that uses P30 antigen, expressed exclusively by tachyzoites (fast multiplying form of the parasite) was used in the present study. Similar commercial ELISA has been previously used for diagnosis of T. gondii infection in sheep and goats with reliable results [31-33]. …”
Section: Discussionmentioning
confidence: 99%
“…ELISA that uses P30 antigen, expressed exclusively by tachyzoites (fast multiplying form of the parasite) was used in the present study. Similar commercial ELISA has been previously used for diagnosis of T. gondii infection in sheep and goats with reliable results [31-33]. …”
Section: Discussionmentioning
confidence: 99%
“…Microscopy revealed changes suggestive of toxoplasma encephalitis characterized by severe congestion, areas of malacia with cysts, tachyzoites, microgliosis ( Figure 3A), fibrinous microthrombosis and lymphocytic meningitis (DA MOTTA et al, 2008). Inflammatory changes characterized by encephalitis, myocarditis and multifocal hepatitis are described in sheep fetuses aborted because toxoplasma infection (DA MOT-TA et al, 2008;EDWARDS;DUBEY, 2013;O'DONOVAN et al, 2012;PEREIRA-BUENO et al, 2004a). In addition, tissue cysts and tachyzoites can be observed in the brain tissue of these fetuses, and tachyzoites are often observed adjacently to the cerebral vascular endothelium (ANWAR et al, 2013;DUBEY, 2010;O'DONOVAN et al, 2012).…”
Section: Pathological Disorders Resulting From Toxoplasma Infection Imentioning
confidence: 99%
“…Inflammatory changes characterized by encephalitis, myocarditis and multifocal hepatitis are described in sheep fetuses aborted because toxoplasma infection (DA MOT-TA et al, 2008;EDWARDS;DUBEY, 2013;O'DONOVAN et al, 2012;PEREIRA-BUENO et al, 2004a). In addition, tissue cysts and tachyzoites can be observed in the brain tissue of these fetuses, and tachyzoites are often observed adjacently to the cerebral vascular endothelium (ANWAR et al, 2013;DUBEY, 2010;O'DONOVAN et al, 2012). Presence of cysts ( Figure 3B) of T. gondii in the brain of an aborted sheep fetus was confirmed by immunohistochemistry (IHC) in the State of Rio Grande do Sul (DA MOTTA et al, 2008).…”
Section: Pathological Disorders Resulting From Toxoplasma Infection Imentioning
confidence: 99%
“…There is also experimental evidence that both T. gondii and N. caninum cause recurrent abortions in chronically infected ewes . Histological studies of aborted foetuses, weak lambs, congenitally infected healthy lambs and experimentally infected ewes show that T. gondii and N. caninum dissemination patterns are quite similar . Aborted T. gondii ‐infected foetuses have lesions primarily in the brain, with some specificity for regions such as the optic tract and rostral margin of the pons .…”
Section: Host Responses To Toxoplasma and Closely Related Species Difmentioning
confidence: 99%
“…Histological studies of aborted foetuses, weak lambs, congenitally infected healthy lambs and experimentally infected ewes show that T. gondii and N. caninum dissemination patterns are quite similar . Aborted T. gondii ‐infected foetuses have lesions primarily in the brain, with some specificity for regions such as the optic tract and rostral margin of the pons . Experimental infection in male sheep (rams) has shown that T. gondii does infect the male reproductive organs , and T. gondii infection can be sexually transmitted from infected rams to uninfected ewes , but this has not been examined with N. caninum infection.…”
Section: Host Responses To Toxoplasma and Closely Related Species Difmentioning
confidence: 99%